Silencing periostin inhibits myofibroblast transdifferentiation of fibrotic buccal mucosal fibroblasts - Jyun-Yang Su; Cheng-Chia Yu; Chih-Yu Peng; Yi-Wen Liao; Pei-Ling Hsieh; Li-Chiu Yang; Chuan-Hang Yu; Ming-Yung Chou (Journal of the Formosan Medical Association, 2021)
Background/Purpose: Oral submucous fibrosis (OSF) a well-recognized oral premalignant disorder. Several studies have demonstrated that periostin, a matricellular protein, is involved in the development and pathogenesis of fibrosis diseases. Nevertheless, the contribution of periostin in OSF remains to be uncovered.The purpose of the study was to illustrate the functional role of periostin involved in OSF pathogenesis. Methods: RNA-sequencing was employed to screen for differentially expressed genes in normal and OSF tissues. Validation of the upregulation of periostin in OSF specimens and fibrotic buccal mucosal fibroblasts (fBMFs) was conducted by qRT-PCR. The correlation of the gene expression of periostin and various fibrosis markers was analyzed. In addition, the functional role of periostin in myofibroblast features was tested using collagen gel contraction and transwell migration assays. Results: We observed overexpression of periostin in OSF specimens using RNA-sequencing and confirmed its upregulation in OSF tissues and patient-derived fBMFs. Besides, there was a positive relationship between the expression of periostin and several fibrosis-associated markers, including ACTA2 (α-smooth muscle actin; α-SMA), COL1A1 (type 1 collagen α1 chain), TGFB1 (TGF-β1), and FN1 (fibronectin). Furthermore, we examined the effect of silencing periostin on the maintenance of myofibroblast characteristics and showed that knockdown of periostin suppressed the expression of α-SMA. Also, inhibition of periostin markedly downregulated the myofibroblast activities (collagen gel contraction and migration capacities). Conclusion: Our results indicate the aberrant expression of periostin in OSF tissues and myofibroblasts. Moreover, the expression of periostin is positively associated with fibrosis markers, and repression of periostin may be a promising direction to alleviate the progression of OSF.